An Analysis of Speech Act Used in Enola Holmes Movie - Mega Putri Agatha Karaeng; Galuh Dwi Ajeng; Hajjah Zulianti; Dian Windriani (Lexeme : Journal of Linguistics and Applied Linguistics, 2024)
Miscommunication about the meaning of words in relation to the context of a situation is a common problem faced by both speakers and hearers. It was interesting in finding out about how language functions in human interaction, taking into account the context that affects communication as well as the intents behind utterances. Then, this research aims to identify the types of speech acts used; the most dominant types; the intended meanings of speech acts employed by Enola Holmes in the movie "Enola Holmes." This study adopts a descriptive qualitative approach, focusing on the utterances of the character Enola Holmes. Utilizing George Yule's theoretical framework for speech act analysis, the findings reveal four categories of speech acts: representatives, expressives, directives, and commissives. The predominant category identified is representative speech acts, accounting for 127 out of 222 instances (57%). The speech acts in the movie serve various purposes, including stating the truth, providing information, narrating life stories, refusing unwanted propositions, expressing adventure and unselfish assistance, showing friendship, making requests, indicating kinship conversing, and expressing amusement or pleasure. This study sheds light on the numerous functions and meanings that language serves for fictional characters in a movie, like Enola Holmes.